IMPROVED OF THE EXPERIMENTING SKILL BY GUIDED INQUIRY LEARNING MODEL ON SCIENCE LEARNING - Nanda Sari Rizki; Kartono Kartono; Hadiyah Hadiyah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This reseach is a Classroom Action Research that purpose to improve the experimenting skill by using Guided Inquiry learning model in grade V studens of Elementary School of academic year 2017/2018. This research conducted in three cycles. Each cycles consist of 2 meeting and includes four component: preparation, action, observation and reflection. Data analysis technique used data collection, data reduction, data presentation and conclution. Data collecting technique used observation, interviews, and documentation. Data validity technique used triangulation source and triangulation technique. Based on the result of the research, it can know that Guided Inquiry model has improved of average score of student’s experimenting skill in cycle I, cycle II and cycle III. In the Precycle average score 41,3 (0%). After used Guided Inquiry model at the meeting 2 of first cycle the average increased to 48,1 (0%). In the meeting 2 of second cycle the average increased to 58,0 (8,33%), In the meeting 2 of third cycle the average increased to 79,5 (83,33%). Based on this research, it can be concluded that the application of Guided Inquiry model can improve the skill of experimenting.